Material Culture Analysis on the Personal Furniture in the Museums of Silay City: Basis for Cultural and Historical Preservation - Tribunal, Ruth; Pedrosa, Evalyn; Alegata, Wayne; Sayson, Ronald John (JPAIR Multidisciplinary Research, 2015)
Culture and history harbor the beauty of one’s society. In view, the study of artifacts could best explain our cultural and historical background. The study aimed to examine the personal furniture in the museums of Silay City to preserve the culture and tradition of the old society in Silay through material culture analysis. The study is a qualitative research conducted within the context of descriptive and historical research. Interview method was used in gathering information. McClung Fleming’s two conceptual tools of artifact analysis were utilized to help distinguish precise information about its five properties. Personal furniture in Manuel Severino Hofilena Ancestral House and Bernardino-Ysabel Jalandoni Museum were examined and analyze. The result showed that the personal furniture in two museums have significant influence in the culture and tradition of every Filipino-Spanish family in Silay. The study concludes that material culture analysis on the personal furniture could help preserve the culture and tradition of the past. The study further recommends that teachers and students can utilize the result of the study as material for understanding literature, culture, and history. Also, the government could use the study as basis for their cultural and historical preservation programs.